Genetic enhancement for superior food-feed traits in a pearl millet (Pennisetum glaucum (L.) R. Br.) variety by recurrent selection - Bidinger, F.R.; Blümmel, Michael; Hash, C.T.; Choudhary, S. (2010)
Grain and stover productivity and variation in stover quality traits were investigated amongst 256 full-sib progenies of pearl millet variety ICMV 221. Substantial ranges were observed for grain (1.5-fold difference) and stover (1.8-fold difference) yields. Stover protein content varied two-fold, ranging from 4.3to 8.6% and stover in vitro digestibilities ranged from 40.7 to 46.1%. Yield of digestible stover ranged from 1132 to 2388 kg ha−1. From these full-sibs experimental varieties were generated targeting through two selection cycles: a) grain yield, b) dual-purpose usage, c) high stover protein; and d) high stover digestibility. Stover from each of the two selection cycles in 2005 and 2006 were tested with sheep for digestibility, intake, digestible organic matter intake and nitrogen balances. Generally traits in the experimental varieties were consistent with their intentional design. Through full-sib recurrent selection considerable gains were achieved in food-feed traits. For example more than a 17% increase was found in digestible organic matter intake in the dual-purpose experimental variety (15.1g Kg−1 LW d−1) compared to the original variety (12.9 g Kg−1 LW d−1). Similarly, nitrogen balance improved from -0.016 g Kg−1 LW d−1 in the sheep fed on stover from the original variety to +0.051 g Kg−1 LW d−1 in sheep fed stover from the experimental dual-purpose variety.